Free radical-mediated intramolecular photocyclization of AIEgens based on 2,3-diphenylbenzo[b]thiophene S,S-dioxide - Guo, Jingjing (2023)
As an important category of photochemical reactions, photocyclization is regarded as an ideal entry point for building intelligent photoresponsive materials. Herein, a series of aggregation-induced emission luminogens (AIEgens) with sensitive photoresponsive behavior are developed based on 2,3-diphenylbenzo[b]thiophene S,S-dioxide (DP-BTO), and the impacts of substituents with different electronic structures are investigated. The comprehensive experimental and computational characterizations reveal that their photoresponsive activity is resulted from triplet diradical-mediated intramolecular photocyclization, followed by dehydrogenation to yield stable polycyclic photoproducts. This photocyclization process is active in solution but suppressed in the solid state, and thus can act as a supplementary nonradiative decay channel for the excited state to contribute to AIE effect. Moreover, the generated triplet diradical intermediates upon light irradiation can effectively inhibit the growth of S. aureus, indicative of their promising application as antibacterial agents. This work provides an in-depth mechanistic description about the photocyclization of DP-BTO derivatives and furnishes a perspective on the correlation of photochemical decay and photophysical property.